2018
DOI: 10.1634/theoncologist.2018-0296
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Event Management in Patients with BRAF V600E-Mutant Non-Small Cell Lung Cancer Treated with Dabrafenib plus Trametinib

Abstract: Therapies for advanced non‐small cell lung cancer (NSCLC) continue to become more sophisticated. Chemotherapeutics are giving way to newer approaches such as immune checkpoint inhibitors and targeted therapies for greater efficacy and improved outcomes. Dabrafenib plus trametinib combination therapy was first approved for the treatment of metastatic melanoma harboring the BRAF V600‐mutation in 2014. In 2017, the U.S. Food and Drug Administration approved the combination for patients with NSCLC with the same mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Studies found that trametinib has a strong activity in cases of BRAF mutation and its combination with dabrafenib has demonstrated substantial clinical activity in patients with the BRAF V600E mutant. That combination is now a standard treatment in the first-line setting (48, 49), although adverse events need to be managed (50). Here, we have studied, for the first time, the combination of trametinib and bosutinib in EGFR-mutant NSCLC, which is a well-characterized and commonly observed type of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that trametinib has a strong activity in cases of BRAF mutation and its combination with dabrafenib has demonstrated substantial clinical activity in patients with the BRAF V600E mutant. That combination is now a standard treatment in the first-line setting (48, 49), although adverse events need to be managed (50). Here, we have studied, for the first time, the combination of trametinib and bosutinib in EGFR-mutant NSCLC, which is a well-characterized and commonly observed type of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 58 patients bearing V600 mutation, the ORR to BRAFi monotherapy and combined BRAFi/MEKi treatment was 27% (6/22) and 56% (20/36), respectively, whereas PFS was 3.7 and 8.0 months, respectively (p = 0.002) [87]. The DESCRIBE II trial has evaluated the effectiveness of BRAFi dabrafenib and trametinib in the treatment of BRAF V600 -mutated metastatic melanoma patients, in a compassionate use setting [88]. This retrospective trial showed substantial clinical activity with dabrafenib plus trametinib in patients with unresectable or metastatic melanoma, similar to what has been assessed in previous prospective controlled trials [89][90][91].…”
Section: Ongoing Clinical Trialsmentioning
confidence: 99%
“…The DESCRIBE II trial has evaluated the effectiveness of BRAFi dabrafenib and trametinib in the treatment of BRAF V600 -mutated metastatic melanoma patients, in a compassionate use setting [ 88 ]. This retrospective trial showed substantial clinical activity with dabrafenib plus trametinib in patients with unresectable or metastatic melanoma, similar to what has been assessed in previous prospective controlled trials [ 89 – 91 ].…”
Section: Introductionmentioning
confidence: 99%
“…112 The significance of dermatologic toxicities is highlighted by the growing number of consensus reports and opinions associated with the prevention, identification, and management of these conditions. 61,103,[329][330][331][332] These recommendations also emphasize the importance of early engagement of dermatologists/ dermatopathologists as part of the multidisciplinary team caring for cancer patients. [333][334][335] In conclusion, increased awareness of the diverse morphologic types of dermatologic toxicities associated with Nibs and a deeper insight into the mechanisms behind the spectrum of distinct and overlapping adverse reactions is critical for patient care in the era of "oncodermatology" and "oncodermatopathology."…”
Section: Discussionmentioning
confidence: 99%